Rapid Prototyping of Ceramic Components - Lenk, R. (Advanced engineering materials, 2000)
A variety of techniques has been recently developed to produce parts and prototypes from a computer‐aided design (CAD) image without hard tools, dies, or molds. Integration of rapid prototyping technologies – laser sintering, multiphase jet solidification, hot molding etc. – into standard ceramic shaping processes is subject of several current research projects. Using a 3D data set describing the geometry of the ceramic component, complex original models have been developed from rapid prototyping techniques. For a small‐production run plastic molds can be used, whereas for a medium‐ or a high‐production run a hardened steel die can be produced based on the correct shrinkage data. No s